Ciprofloxacin resistance in domestic wastewater treatment plants - Manaia, Célia M. (2010)
The potential of domestic wastewater treatment plants to contribute for the dissemination of ciprofloxacin-resistant bacteria was assessed. Differences on bacterial counts and percentage of resistance in the raw wastewater could not be explained on basis of the size of the plant or demographic characteristics of population served. In contrast, the treated effluent of the larger plants had significantly more heterotrophs and enterobacteria, including ciprofloxacin-resistant organisms, than the smaller (p<0.01). Moreover, longer hydraulic retention times were associated with significantly higher percentages of resistant enterobacteria in the treated effluent (p<0.05). Independently of the size or type of treatment used, domestic wastewater treatment plants discharged per day at least 1010–1014 colony forming units of ciprofloxacin-resistant bacteria into the receiving environment.